2018
DOI: 10.1007/s10745-018-0038-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Climate and Social Changes on Cloudberry (Bakeapple) Picking: a Case Study from Southeastern Labrador

Abstract: The traditional subsistence activities of Indigenous communities in Canada’s subarctic are being affected by the impacts of climate change, compounding the effects of social, economic and political changes. Most research has focused on hunting and fishing activities, overlooking berry picking as an important socio-cultural activity and contributor to the diversity of food systems. We examined the vulnerability of cloudberry (referred to as ‘bakeapple’ consistent with local terminology) picking to environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…One key impact that could threaten WFP use is the likely shifts in both WFP geographic ranges and phenological changes in ripening times. This could create mismatches with traditional knowledge and practices of the communities that traditionally harvest them [ 117 ].…”
Section: The Importance Of Wild Food Plants Todaymentioning
confidence: 99%
“…One key impact that could threaten WFP use is the likely shifts in both WFP geographic ranges and phenological changes in ripening times. This could create mismatches with traditional knowledge and practices of the communities that traditionally harvest them [ 117 ].…”
Section: The Importance Of Wild Food Plants Todaymentioning
confidence: 99%
“…In the Labrador region of northeastern Canada, continental-to hemispheric-scale studies have depicted peatland permafrost as present in the region's continental interior but as far less abundant or completely absent along most of the Labrador Sea coastline (Fewster et al, 2020;Hugelius et al, 2020;Olefeldt et al, 2021). However, historic and contemporary use of coastal peatland permafrost environments by Labrador Inuit and Innu is well documented (Anderson et al, 2018), and published field-based observations (e.g., Anderson et al, 2018;Andrews, 1961;Brown, 1975Brown, , 1979Davis et al, 2020;Dionne, 1984;Elias, 1982;Hustich, 1939;Seguin and Dionne, 1992;Smith, 2003;Wenner, 1947) suggest that peatland permafrost is abundant along some sections of the coast. This recurring misestimation of peatland permafrost occurrence has an impact on predictions of ground ice content (O'Neill et al, 2019), thermokarst potential (Olefeldt et al, 2016), and carbon content (Hugelius et al, 2014) in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing and projected climate changes in high latitudes may, however, change these functions as plants respond to a changing environment (Gauthier et al, 2015). Although the extended growing season may improve yields (Holmberg et al, 2019), the sensitivity of these plants to climate and environmental changes (Boulanger-Lapointe et al, 2017;Anderson et al, 2018;Herman-Mercer et al, 2020) may lead to changes in the areas where they are found. The influence of climate change on berry abundance has been recognized by local residents in northeastern Siberia (Ksenofontov et al, 2018) and Alaska (Hupp et al, 2015).…”
Section: Introductionmentioning
confidence: 99%